Online humour as a community-building cushioning glue - Vittorio Marone (The European Journal of Humour Research, 2015)
This article examines the uses and functions of humour in an online community of gamers and nonprofessional game designers who present and critique user-generated artefacts created with the popular game series LittleBigPlanet. Findings show that participants use humour and “good humour” to achieve a variety of social goals: to veil statements of ability and effort, alleviate negative comments, present user-generated content, attract new players, support other participants, and overall engender a smiling atmosphere that incentives collaboration, peer feedback, and social cohesion. Far from being a trivial ornament, humour emerges as a community building “cushioning glue” that connects, seals, and buffers different gears of computer-mediated interaction, contributing to defining the boundaries and the identity of the analysed online space.